Opini Publik Kasus Korupsi Nurdin Abdullah di Kanal Youtube KPK RI - Sultan, Badrul Aeni; Hasrullah; Mau, Muliadi (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2023)
The arrest of Nurdin Abdullah, who is the Governor of South Sulawesi Province for the 2018-2023 period by the Corruption Eradication Commission (KPK) of the Republic of Indonesia, has brought public opinion to the public. This is because Nurdin Abdullah is one of the outstanding regional heads in Indonesia, he was the recipient of the Bung Hatta Anti-Corruption Award (BHACA) in 2017. The Bantaeng Regent for the 2008-2018 period was forgotten to commit various violations in administering the government in South Sulawesi Province. In various corruption cases, the Indonesian Corruption Eradication Commission in every legal process always uses YouTube as a publication. Youtube as a mass media opens space for the public to comment on issues, this is supported by the presence of new media theories. Therefore, researchers are interested in examining this problem with the formulation of the problem, how is the public opinion of Nurdin Abdullah's corruption on the KPK RI youtube channel, where the research is an entire commentary that made 379 comments, with quantitative methods. The results of the study show that the tendency of public opinion towards the Nurdin Abdullah case is positive comments with a presentation of 44.9%, negative 36.9%, and neutral 18.2%, with the most comments topics focused on corruption cases with a presentation of 52.2%. which was then followed by a discussion about the persona of Nurdin Abdullah 35.1%.